Gizi Buruk Tipe Marasmus dengan Hydranencephaly dan Anemia Defsiensi Besi pada Anak Usia 8 Tahun 5 Bulan - Andi Husni Esa Darussalam (Syntax Idea)
This study discusses the case of an 8-year and 5-month-old child suffering from marasmus-type malnutrition, hydranencephaly, and iron-deficiency anemia simultaneously. This case highlights the complexity of health issues faced by children in various regions with limited access to medical care and adequate nutrition. The study includes an in-depth analysis of the risk factors that may have led to the child's malnutrition and iron-deficiency anemia. Clinical data, anthropometric measurements, and laboratory results were analyzed to gain a better understanding of the causes and effects of malnutrition and anemia on this child's development. The findings from this research provide crucial insights into the need for efforts to prevent malnutrition and iron-deficiency anemia in children, especially in areas with challenges in accessing healthcare and nutrition. This study also underscores the importance of a multidisciplinary approach in caring for children with complex health conditions, as seen in this case. The implications of this research can help guide clinical practices and public health programs focused on improving children's health and addressing nutrition-related issues.